Integration of Learning Styles and Higher Order Thinking Skills among Technical Students - Heong, Yee Mei; Hie Ping, Kong; Hamdan, Nuraffefa; Boon Ching, Kok; Md. Yunos, Jailani; Mohaffyza Mohamad, Mimi; Kee Jiar, Yeo; Azid, Nurulwahida (Journal of Technical Education and Training, 2020)
Learning styles and higher order thinking skills (HOTS) play an important role in higher education learning. They represent different individual preferences and strengths in learning and can be a stimuli for developing new ways of learning. This is because KBAT can increase an individualâ€™s ability to observe and process new information while learning style is a method of observation and process the information that occurs in the individual. The purpose of this research was to identify the pattern of Kolb Learning Styles among the technical students based on demographic factors and identify the patterns of Marzano HOTS usage based on Kolb learning styles. The design of this study was descriptive with a quantitative approach. A total of 163 technical students from Faculty of Civil and Environmental Engineering at University Tun Hussein Onn Malaysia (UTHM) were random cluster selected as samples. The Kolb Learning Styles Inventory and assessment rubric were used as research instruments. The findings indicated that the most dominant learning style among technical students is Doer and followed by Feeler, Thinker and Watcher. The patterns of learning styles based on demographic factors are the same. The findings showed that the most widely used Marzano HOTS by all four types of Kolb Learning Styles are comparison and induction. Besides that, the findings revealed that there is no statistically significant difference in Kolb Learning Styles on the usage of Marzano HOTS. Therefore, the differences in learning styles do not affect the usage of HOTS. The implication of the integration of Kolb’s learning styles and HOTS Marzano have the potential to bring two simultaneous benefits to students in terms of achievement of ideas generation.